Pointwise Structure–Function Analysis of the Ellipsoid Zone in Retinitis Pigmentosa Using an Artificial Intelligence-Assisted OCT and Microperimetry Overlay - Jesse A. Most, BA; An D. Le, MS, PhD; Melanie D. Tran, BS; Evan H. Walker, MS; Aneesh Swamy; Dirk-Uwe G. Bartsch, PhD; William R. Freeman, MD; Truong Nguyen, PhD; Cheolhong An, PhD; Shyamanga Borooah, MBBS, PhD (Ophthalmology Science)
Objective: To perform a pointwise structure–function analysis of the ellipsoid zone (EZ) in retinitis pigmentosa (RP) using an artificial intelligence–based overlay to understand EZ structure–function relationships. Design: A single-center retrospective study. Subjects: Patients with clinically confirmed RP. Methods: Same-day spectral-domain OCT (SD-OCT) and microperimetry near-infrared images were overlaid in patients with confirmed RP. Overlay used a coarse alignment artificial intelligence model. Each locus, on a 68-point microperimetry grid spanning the central 20° of the macula, was identified on individual SD-OCT B-scans. Ellipsoid zone structure was graded at each locus on a 3-point scale: grade 0 = EZ not visible; grade 1 = EZ attenuated; grade 2 = EZ normal. Ellipsoid zone grades were correlated with microperimetry sensitivity scores recorded in decibels (dB). Main Outcome Measures: Correlation of EZ integrity on SD-OCT with microperimetric retinal sensitivity. Results: Fifty-one eyes from thirty-one patients with RP were included in the analysis, with 60 total overlays, including follow-up studies, resulting in 3985 test loci being graded. Patients had a mean age of 39.4 (32.8–46.0) years, with 41.9% being female. Mean best-corrected visual acuity was 0.166 (0.129–0.203) logarithm of the minimum angle of resolution. The overall mean sensitivity (MS) was 9.72 (7.32–12.12) dB, whereas MS was 6.02 (4.06–7.98) dB for grade 0 loci, 18.36 (16.35–20.36) dB for grade 1 loci, and 20.90 (18.87–22.93) dB for grade 2 loci. Differences in MS were significant between graded groups (P < 0.001). Correlation between EZ grade and sensitivity was 0.65 (0.64–0.67), whereas correlation of sensitivity with distance from the fovea was −0.41 (−0.43 to −0.39). Focusing on grade 0 loci, 57.5% had sensitivity scores >0 dB, and 4% had scores ≥20 dB, suggesting that these points had function despite no observable EZ on SD-OCT. Conclusions: We identified local EZ structure–function incongruencies in RP using a pointwise analysis of structure–function overlay. These loci of interest may be overlooked in analyses that average across the visual field. Preserved photoreceptor function, in the absence of visibly intact EZ, warrants further investigation. Financial Disclosure(s): Proprietary or commercial disclosure may be found in the Footnotes and Disclosures at the end of this article.